RegX3-Mediated Regulation of Methylcitrate Cycle in Mycobacterium smegmatis - Pei, Jin-Feng; Qi, Nan; Li, Yu-Xin; Wo, Jing; Ye, Bang-Ce (Frontiers in Microbiology, 2021)
Mycobacterium tuberculosis is a global human pathogen that infects macrophages and can establish a latent infection. Emerging evidence has established the nutrients metabolism as a key point to study the pathogenesis of M. tuberculosis and host immunity. It was reported that fatty acids and cholesterol are the major nutrient sources of M. tuberculosis in the period of infection. However, the mechanism by which M. tuberculosis utilizes lipids for maintaining life activities in nutrient-deficiency macrophages is poorly understood. Mycobacterium smegmatis is fast-growing and generally used to study its pathogenic counterpart, M. tuberculosis. In this work, we found that the phosphate sensing regulator RegX3 of M. smegmatis is required for its growing on propionate and surviving in macrophages. We further demonstrated that the expression of prpR and related genes (prpDBC) in methylcitrate cycle could be enhanced by RegX3 in response to the phosphate-starvation condition. The binding sites of the promoter region of prpR for RegX3 and PrpR were investigated. In addition, cell morphology assay showed that RegX3 is responsible for cell morphological elongation, thus promoting the proliferation and survival of M. smegmatis in macrophages. Taken together, our findings revealed a novel transcriptional regulation mechanism of RegX3 on propionate metabolism, and uncovered that the nutrients-sensing regulatory system puts bacteria at metabolic steady state by altering cell morphology. More importantly, since we observed that M. tuberculosis RegX3 also binds to the prpR operon in vitro, the RegX3-mediated regulation might be general in M. tuberculosis and other mycobacteria for nutrient sensing and environmental adaptation.